Enhancing cybersecurity: A high-performance intrusion detection approach through boosting minority class recognition - Chadia E. L. Asry; Ibtissam Benchaji; Samira Douzi; Bouabid E. L. Ouahidi (PLoS ONE, 2025)
The swift proliferation and extensive incorporation of the Internet into worldwide networks have rendered the utilization of Intrusion Detection Systems (IDS) essential for preserving network security. Nonetheless, Intrusion Detection Systems have considerable difficulties, especially in precisely identifying attacks from minority classes. Current methodologies in the literature predominantly adhere to one of two strategies: either disregarding minority classes or use resampling techniques to equilibrate class distributions. Nonetheless, these methods may constrain overall system efficacy. This research utilizes Shapley Additive Explanations (SHAP) for feature selection with Recursive Feature Elimination with Cross-Validation (RFECV), employing XGBoost as the classifier. The model attained precision, recall, and F1-scores of 0.8095, 0.8293, and 0.8193, respectively, signifying improved identification of minority class attacks, namely “worms,” within the UNSW NB15 dataset. To enhance the validation of the proposed approach, we utilized the CICIDS2019 and CICIoT2023 datasets, with findings affirming its efficacy in detecting and classifying minority class attacks.